Linguistic and Cultural Adaptation of a Self-Determination Scale for People with Intellectual Disabilities - Lilian Castro-Durán; Gloria Sanzana-Vallejos; Viviana Vallejos-Garcías; Rafael Zapata-Lamana; Ana Mendoza-Mardones; Loreto Dávila-Opazo; Javiera Duhart-Carrión; Inti Huaiquipan-Ortega; Igor Cigarroa; Edmundo Espejo-Sepúlveda; Misael Sandoval-Cárcamo (Disabilities)
The main objectives of this study were to adapt the AUTODDIS scale to the cultural and social dimensions of Chile and to analyze its reliability and validity. The reliability and validity were assessed through a pilot study conducted with a population of students with intellectual disabilities (ID). The linguistic adaptation was executed according to expert judgments of each indicator: adequacy, coherence, relevance, and clarity. After the scale adaptation, a scale pilot was conducted to explore its technical properties. It was performed in a public school for students with ID. The validity coefficient result was 0.998, while the complete reliability result was α = 0.978. For the reliability subscales, the results were the following: autonomy α = 0.941, self-initiation α = 0.925, self-direction α = 0.970, self-regulation α = 0.804, and self-concept α = 0.935. The results confirm the AUTODDIS scale as a valid and reliable instrument to evaluate self-determination. However, it is necessary to apply this scale to a larger number of students with ID to generalize these results.